Therapeutic Alliance in COVID-19 Era Remote Psychotherapy Delivered to Physically Ill Patients With Disturbed Body Image - Grignoli, Nicola; Arnaboldi, Paola; Antonini, Mattia (Frontiers in Psychology, 2021)
The COVID-19 pandemic outbreak has led to a general reorganization of health services and an increase in outpatient telemedicine in mental healthcare for physically ill people. Current literature highlights facilitators and obstacles concerning the use of new technologies in psychotherapy, an underrated topic of research in the context of supportive expressive psychotherapy. More insight is needed to explore the characteristics of video in therapeutic alliance for treatment of specific mental disorders experienced in psychosomatics, particularly with people suffering from a disturbed body- and self-image. Using two clinical vignettes, it is the authors’ intention to enrich the critical debate on current knowledge in psychosomatic remote psychotherapy, with special focus on mentalization deficits and their impact on therapeutic alliance in the consultation-liaison psychiatry setting. In particular, we will question the interpersonal processes at stake related to mirroring and the disruption caused by the use of videoconference applications. We will also reflect upon the relationship between the therapeutic alliance and the medical team, and that between patient and psychotherapist. The aim is to improve psychotherapeutic alliance maintained during the pandemic for specific mental disorders and to inform about possible clinical factors that could be the subject of future empirical studies or professional guidelines.